Urgent COVID-19 Vaccination of Healthcare Workers via a Quality Improvement Initiative. Issue 6 (29th November 2021) - Baumer-Mouradian, Shannon H.; Collins, Stacey; Lausten, Thomas; Pohl, Cecile; Sisney, Mary; Khare, Smriti; Ose, Megan; Roe, Jennifer; Reilly, Chelsi; Gutzeit, Michael
Abstract : Supplemental Digital Content is available in the text. Abstract : Introduction: The COVID-19 pandemic has posed a significant threat to US healthcare workers' mental and physical health. The US Food and Drug Administration approved the first mRNA COVID-19 vaccine for Emergency Use Authorization on December 11, 2020. High-risk healthcare workers were determined to be Phase 1a. Goal: Complete the two-dose vaccine series in all interested phase 1a staff immediately after the COVID-19 vaccine was available and distributed to our institution, December 14, 2020. Methods: A multidisciplinary team involving key stakeholders performed process mapping to develop four key drivers for vaccination success: rapid vaccine procurement, proper storage and handling, well-defined vaccine administration and follow-up plan, and system preparation. We tested interventions using plan-do-study-act cycles. We included employees and providers with direct patient care responsibilities, age 18 years or older, employed at the children's health system, or the affiliated academic medical center. We examined the total number of dose 1 and dose 2 vaccines administered for our primary outcome, and the balancing measure included the percent of wasted vaccines. Results: Three thousand nine-hundred twenty-one healthcare personnel completed the survey, and 73% reported intent to receive the COVID-19 vaccine immediately or at a later time. After 57 clinic days, we vaccinated 83% (n = 5, 231) of healthcare personnel at our institution, and 99% completed the two-dose series. Due to surplus vaccines, we vaccinated an additional 1, 258 community members with 99% completion of the two-dose series. Vaccine waste was minimal 0.1%. Conclusion: We describe the development and implementation of a successful COVID-19 employee and community vaccination program.